Study of applying fiber based laser with the primary standard for optical power and improvement of spectral responsivity scales in near IR range - Zhang, Jing (2014)
A fiber optics based 1310nm laser was applied with the primary standard cryogenic radiometer for optical power measurement to extend NMC’s spectral responsivity scale toward infrared wavelength. The absolute optical power was measured and two absolute transfer standard detectors (InGaAs based trap detectors) were calibrated at 1310nm. The measurement setup is described and the measurement uncertainty was analyzed. The advantages of using fiber optics based laser sources are discussed in the paper. With the new calibration capability, the uncertainty of the spectral responsivity in the range from 900nm to 1640nm in NMC will be improved.